A Conceptual Framework for a Training Curriculum on Natural Disaster Risk Reduction and Management for Agriculture and the Rural Space - Anderlini, Sanam (World Bank, Washington, DC, 2016)
This paper presents the conceptual framework for a training program on integrating disaster risk reduction and climate-change mitigation into Agriculture and Rural Development Department (ARD) programming. Its target audience consists of World Bank task team leaders and their national counterparts and partners working in agriculture and rural settings.